Intestinal anti-inflammatory effects of goat whey on DNBS-induced colitis in mice. - Daline F S Araújo; Gerlane C B Guerra; Maria Manuela E Pintado; Yasmim R F Sousa; Francesca Algieri; Alba Rodriguez-Nogales; Raimundo F Araújo; Julio Gálvez; Rita de Cássia R E Queiroga; Maria Elena Rodriguez-Cabezas (PLoS ONE, 2017)
This study evaluated the intestinal anti-inflammatory effects of goat whey in a mouse model of colitis induced by 2,4-dinitrobenzenesulfonic acid that resembles human IBD. At a concentration of 4 g/kg/day, the goat whey improved the symptoms of intestinal inflammation, namely by decreasing the disease activity index, colonic weight/length, and leukocyte infiltration. Moreover, goat whey inhibited NF-κB p65 and p38 MAPK signaling pathways and consequently down-regulated the gene expression of various proinflammatory markers such as IL-1β, IL-6, IL-17, TNF-α, iNOS, MMP-9, ICAM-1. Also, goat whey increased the expression of proteins such as mucins, occludin proteins and cytokine signalling suppressors. The immunomodulatory properties of goat whey were also evaluated in vitro using the murine macrophage cell line Raw 264 and CMT-93 cells derived from mouse rectum carcinomas. The results revealed the ability of goat whey to inhibit the production of NO and reduce IL-6 production in LPS-stimulated cells. In conclusion, goat whey exhibited anti-inflammatory effects in the DNBS model of intestinal inflammation, and these observations were confirmed by its immunomodulatory properties in vitro. Together, our results indicate that goat whey could have applications for the treatment of IBD.